IMPLEMENTASI KEBIJAKAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DI PEMERINTAH NAGARI CUPAK KABUPATEN SOLOK TAHUN 2021-2023 - Putri, Medina Permata; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study discusses the implementation of the Electronic-Based Government System (SPBE) policy in the Government of Nagari Cupak during the period of 2021 to 2023. The background of this research is based on the importance of digital transformation in government administration, especially at the nagari (village) level, in order to achieve governance that is transparent, accountable, efficient, and responsive to community needs. SPBE is one of the government's strategies to improve the quality of public services through the integrated use of information and communication technology. This research employs the policy implementation theory of George Edward III, which includes four key variables: communication, resources, disposition, and bureaucratic structure. The research method used is a descriptive qualitative approach, with data collected through interviews and documentation. The results of the study show that the implementation of SPBE in Nagari Cupak has not yet run optimally. Although there has been progress in the digitalization of public services, the implementation process still faces several challenges. In terms of communication, there are obstacles in the consistent and comprehensive dissemination of policy information between the nagari government and the community. In terms of resources, there is a lack of skilled human resources and limited budget availability. The disposition of government officials is generally supportive, but public understanding of digital systems remains low, with many residents preferring conventional methods over online systems. The bureaucratic structure, which remains largely traditional, also affects the speed and effectiveness of SPBE implementation. These findings indicate that the success of SPBE policy implementation requires stronger support in the areas of coordination, capacity-building for government personnel, and public training. With improvements in these aspects, SPBE has significant potential to drive a more responsive and modern transformation of local governance at the nagari level. Keywords: Implementation, Electronic-Based Government, Nagari Government